Decomposition of ilmenite by ZnO/ZnS: Enhanced leaching in acid solutions - Arachchi, N.D.H.; Peiris, G.S.; Shimomura, M.; Jayaweera, P.M. (Hydmmetallurgy, 2016)
Attached

Acid leaching of ilmenite (FeTi03) obtained from beach sand was found to be more effective when roasted with ZnO or ZnS at 900 °C. Remarkably higher- iron and titanium leaching rates were observed when compared with normal ilmenite in 5.0 M HC1 at 30 °C,'and 6.0 M H2SO4 at 110 °C, respectively. Roasting of ilmenite with ZnO or ZnS converts acid resistant FeTiOj to more reactive Fe20 3 and Zn2Ti04, resulting in enhanced leaching. Roasting FeTi03 with ZnS generates S02 as a byproduct, which can be used to produce H2S04 acid required in the sulfate process. Added ZnO or ZnS can be recovered as ZnO, therefore the overall process acts as a catalytic decomposition of FeTi03. Ores containing ZnS, such as sphalerite, are possible raw materials instead of ZnS, in a commercial application. XRD analysis confirms the formation of zinc titanate, and XPS results indicate the presence of both Fe2x/Fe3+ in naturally weathered ilmenite.
Keywords: Ilmenite; XPS; XRD; acid leaching; roasting; ZnO/ZnS